IMPLEMENTASI DIMENSI DAN TIPE “POLICY NETWORK” DALAM PENANGGULANGAN KEMISKINAN DI KABUPATEN LOMBOK TIMUR - KABUL, LALU MUH. (Universitas Mahasaraswati K. Mataram, 2024)
In the study it’s described implementation of poverty alleviation by using new approach namely dimention and type of “policy network. The study method used is mixed method, integration of quantitative and qualitative. The result of study showed that poor household shoud be identified by Integrated Data Base (IDB) which focus on 40 percent of household group which have lowest welfare rate by using Decil (D) approach namely D1 to D4. Meanwhile, acceleration of poverty alleviation its connected with 7 dimentions of policy network namely actors, function, stucture, institutionalisation, power relations, rule of conduct, and actor strategies and each dimention is heterogen.